FUNCTIONS OF PROFESSIONAL COMPETENCE OF THE FUTURE ENGLISH TEACHER (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The article discusses in detail the reform of the education system, the changes in the training of modern personnel, the presence of certain pedagogical competencies, in particular, their multifunctionality, which, in particular, the professional qualifications and versatility of the English teacher are in the greatest demand today, since this paves the way for the progressive development of English language skills, ensuring the global competitiveness of education, taking a leading position in the quality of general education and training of well-rounded socially responsible personnel, in turn, the need to modernize the pedagogical education system is associated with the fundamental changes taking place in it, and the problem of developing the professional skills and multifunctionality of teachers as subjects of the development of the education system in the modern information society is becoming especially relevant, requiring the formation of their ability to perform their professional tasks and functions at a sufficiently high level.